HYSTEROTHYLACIUM CARUTTI N.SP. (NEMATODA : ANISAKIDAE) FROM THE MARINE FISH JOHNIUS CARUTTA BLOCH OF BAY OF BENGAL (VISAKHAPATNAM) - RAJYALAKSHMI, I; RAO, K. HANUMANTHA; SHYAMASUNDARI, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
The present paper deals with the description of a new species of anematode of the family Anisakidae Railliet. & Henry, 1912 from the body cavity of marine fish Johnius Carutta Bloch from Bay of Bengal (Visakhapatnam). These specimens do not agree with the description of the hitherto described species of the genus. Hence a detailed description and status of the specimens are given in this paper. Description is based on two males and three female specimens from a large number of hosts examined. The new species is characterized by body size, location of nerve ring and excretory pore, length of ventriculus, oesophageal appendix and intestinal caecum, spicules length, number and arrangement of caudal papillae, vulva position and shape of tail.